The Role of Leadership in Improving Work Engangement to Support Sustainability at PT INKA Multi Solusi - Rahmawati, Hasna Lutfia; Restin Meilina (PT. Anagata Sembagi Education, 2025)
This study aims to analyze the role of leadership in increasing work engagement to support the sustainability of the company in PT INKA Multi Solusi. The research uses a descriptive qualitative method with triangulation techniques of data sources in the form of interviews, observations, and documentation. Research informants involve leaders and staff who are directly related to human resource management. The results of the study show that democratic and empowering leadership styles have a significant contribution in increasing the dimensions of work engagement, namely vigor, dedication, and absorption. Effective leadership also strengthens team communication and creates a work environment that supports the company's sustainability. This study contributes to the literature by showing how empowering leadership styles can influence work engagement in the context of manufacturing companies in Indonesia, especially PT INKA Multi Solusi. The results of the study provide insights for companies to adopt a more inclusive leadership style, support individual development, and strengthen collaboration between divisions to improve work engagement and company sustainability. The results of the study provide insights for companies to adopt a more inclusive leadership style, support individual development, and strengthen collaboration between divisions to improve work engagement and company sustainability.